Global Financial Deregulation: Commercial Banking at the Crossroads. - Bohannon, John C.; Swary, Itzhak; Topf, Barry (Journal of Finance, 1992)
Overview Switzerland The Federal Republic of Germany France The United Kingdom Japan Canada The United States securitization and financial innovation non-banking activities of banking organizations the international convergence of capital adequacy requirements the 1992 single European market in financial services trends and developments concluding remarks.